The steward leader : transforming people, organizations and communities - Rodin, R. Scott, 1957- (Downers Grove, Ill. : IVP Academic, 2010)
Everyone has a different idea of what a leader should be. How can any one person be everything? Scott Rodin brings unity and clarity to this confusing, demanding picture of leadership. He offers a comprehensive model that brings together a biblical understanding of holistic stewardship with the best in leadership studies. --from publisher description
Pt. 1. Becoming a steward leader of no reputation -- Pt. 2. Three foundations. Leading in the image of the triune God ; The freedom of the steward leader ; The distinctiveness of the steward leader -- Pt. 3. Four transformations and four trajectories. Stewards of our relationship with our creator God ; Stewards of our relationship with ourselves ; Stewards of our relationship with our neighbor ; Stewards of our relationship with God's creation.
Includes bibliographical references (p. [193]-194) and index.
Keywords: Leadership -- Religious aspects -- Christianity; Christian stewardship